2021
DOI: 10.1007/s13238-021-00838-7
|View full text |Cite
|
Sign up to set email alerts
|

Homology-based repair induced by CRISPR-Cas nucleases in mammalian embryo genome editing

Abstract: Recent advances in genome editing, especially CRISPR-Cas nucleases, have revolutionized both laboratory research and clinical therapeutics. CRISPR-Cas nucleases, together with the DNA damage repair pathway in cells, enable both genetic diversification by classical non-homologous end joining (c-NHEJ) and precise genome modification by homology-based repair (HBR). Genome editing in zygotes is a convenient way to edit the germline, paving the way for animal disease model generation, as well as human embryo genome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 149 publications
(287 reference statements)
1
19
0
Order By: Relevance
“…Cas9 specificity also relies on recognition of a short sequence (NGG) downstream of the gRNA, known as the protospacer adjacent motif (PAM), which is required for opening the DNA and target cleavage (Nishimasu et al., 2014; Sternberg, Redding, Jinek, Greene, & Doudna, 2014). After introduction of a DSB, two major DNA repair mechanisms can intervene: non‐homologous end joining (NHEJ) and homology‐directed repair (HDR) (Saleh‐Gohari & Helleday, 2004; Urnov, Rebar, Holmes, Zhang, & Gregory, 2010; Zhang, Li, Ou, Huang, & Liang, 2021). The first knocks out the targeted gene by generating nonspecific mutations (insertions/deletions, commonly known as indels) and tends to be error‐prone, while the second produces specific modifications determined by an exogenous donor template.…”
Section: Introductionmentioning
confidence: 99%
“…Cas9 specificity also relies on recognition of a short sequence (NGG) downstream of the gRNA, known as the protospacer adjacent motif (PAM), which is required for opening the DNA and target cleavage (Nishimasu et al., 2014; Sternberg, Redding, Jinek, Greene, & Doudna, 2014). After introduction of a DSB, two major DNA repair mechanisms can intervene: non‐homologous end joining (NHEJ) and homology‐directed repair (HDR) (Saleh‐Gohari & Helleday, 2004; Urnov, Rebar, Holmes, Zhang, & Gregory, 2010; Zhang, Li, Ou, Huang, & Liang, 2021). The first knocks out the targeted gene by generating nonspecific mutations (insertions/deletions, commonly known as indels) and tends to be error‐prone, while the second produces specific modifications determined by an exogenous donor template.…”
Section: Introductionmentioning
confidence: 99%
“…In this strategy, the use of dsDNA as donor DNA produces false-positive cell clones via direct transcription and translation or via random integration into the genome through canonical NHEJ (c-NHEJ) [ 15 ]. Recent studies have demonstrated that ssDNA donors show superior performance compared to dsDNA donors in mammalian systems by reducing the probability of NHEJ [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
“…In this strategy, the use of dsDNA as donor DNA produces false-positive cell clones via direct transcription and translation or via random integration into the genome through canonical NHEJ (c-NHEJ) 14 . Recent studies have demonstrated that ssDNA donors show superior performance compared to dsDNA donors in mammalian systems by reducing the probability of NHEJ 15 .…”
Section: Resultsmentioning
confidence: 99%